Oxidative stress and antioxidant imbalance in ovulation disorder in patients with polycystic ovary syndrome - Li, Wenqian; Liu, Chang; Yang, Qingmei; Zhou, Ying; Liu, Min; Shan, Hongying (Frontiers in Nutrition, 2022)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease that is characterized by oligo-ovulation or anovulation, hyperandrogenism, and polycystic ovaries observed using ultrasound with high clinical heterogeneity. At present, the etiology of PCOS is not clear but is thought to be related to genetic, metabolic, endocrine and environmental factors. Hyperandrogenism interacts with insulin resistance and overweight / obesity, forming a vicious cycle of mutual promotion and participating in the occurrence and progression of PCOS. Oxidative stress (OS) refers to the imbalance between the oxidation system and antioxidation system in the human body, which is associated with the occurrence and development of various diseases. Recent studies have shown that OS may be closely related to ovulation disorders in PCOS, and antioxidants can improve the oxidative stress state of PCOS. However, previous studies did not examine the effect of the interaction between OS and hyperandrogenism, insulin resistance or overweight / obesity on ovulation disorders in PCOS. This article reviews the interaction between OS and hyperandrogenism, insulin resistance and overweight / obesity; the effects of OS, hyperandrogenism, insulin resistance and overweight / obesity on ovulation disorders in PCOS; and the application of antioxidants in PCOS.